Equity and Private Debt Markets in Central America, Panama, and the Dominican Republic - Shah, Hemant (IMF Working Papers; Working Paper ;, 2007)
This study focuses on equity, private debt, and asset-backed securities markets in Central America. These markets are generally under-developed throughout the region due to several structural problems, economic and political factors, and weaknesses in regulation and in institutional investor base. The paper identifies key country-specific recommendations to strengthen securities laws, regulatory oversight, market infrastructure, investor base, and new products such as asset-backed securities. Despite these efforts, developing seven viable private capital markets is a difficult goal. The paper thus also explores the benefits and difficulties of creating a single capital market in a region still short of full economic integration.